Success in academic surgery part 1 - Kao, Lillian S. (Springer, 2012)
How does one become a successful academic surgeon?  The Association for Academic Surgery  has been teaching this to medical students, residents, and young faculty for the over 20 years and this is the first time the experience and lessons learned have been summarized in a book format.  Success in Academic Surgery, Part 1, reinforces the curriculum of the Association for Academic Surgery courses and also provides guidance to individual surgeons who have not had the opportunity to attend these courses. Thus, this book is a valuable reference for medical students, surgical residents, and young surgical faculty.